Effect of lycopene on environmental toxicity and pollution induced by PFOS. Issue 4 (July 2021) - He, Yinni; Tang, Juan; Liu, Qingguo
Abstract: Objective: Intend to observe the effect of lycopene on reproductive toxicity induced by PFOS in male rats and its possible mechanism. Methods: 30 male SD rats were randomly divided into 5 groups with 6 rats in each group. The control group was given CMC-Na solution. At the same time, the PFOS group and the low, middle and high dose LP protection groups were fed with poisoned feed (32mg/kg PFOS-K).In the meanwhile, the lycopene protection groups were given LP every other day according to their designed dose, and were killed continuously for 3 months. In addition, the sperm motility, number, LDH-X, CAT, GSH-Px, SOD enzyme activity and MDA content were detected and observed. Results: The sperm motility was 44.00%, 53.68% and 58.37%, respectively.The rate of sperm deformity decreased, and the levels of LDH-X and serum testosterone (T) recovered in varying degrees. Moreover, low, middle and high doses of LP could significantly restore the activities of SOD and CAT and reduce the content of MDA, which was significantly different from that of PFOS group (P<0.05). Conclusion: 10∼20mg/kg LP can protect against reproductive damage induced by subchronic low dose PFOS. In addition, antioxidant damage and regulation of testosterone secretion are important mechanisms for LP to protect reproductive damage induced by PFOS.